Contribution of organic amendments to soil organic matter detected by thermogravimetry. Issue 5 (2nd July 2018) - Tokarski, David; Kučerík, Jiří; Kalbitz, Karsten; Demyan, Michael Scott; Merbach, Ines; Barkusky, Dietmar; Ruehlmann, Joerg; Siewert, Christian
Abstract: Sustainable soil management requires reliable and accurate monitoring of changes in soil organic matter (SOM). However, despite the development of improved analytical techniques during the last decades, there are still limits in the detection of small changes in soil organic carbon content and SOM composition. This study focused on the detection of such changes under laboratory conditions by adding different organic amendments to soils. The model experiments consisted of artificially mixing soil samples from non‐fertilized plots of three German long‐term agricultural experiments in Bad Lauchstädt (silty loam), Grossbeeren (silty sand), and Müncheberg (loamy sand) with straw, farmyard manure, sheep faeces, and charcoal in quantities from 3 to 180 t ha −1 each. In these mixtures we determined the organic carbon contents by elemental analysis and by thermal mass losses (TML) determined by thermogravimetry. The results confirmed the higher reliability of elemental analysis compared to TML for organic carbon content determination. The sensitivity of both methods was not sufficient to detect the changes in organic carbon content caused by small quantities of organic amendments (3 t ha −1 or 0.1–0.4 g C kg −1 soil). In the case of elemental analysis, the detectability of changes in carbon content increased with quantities of added amendments, but the method could not distinguish different types of organic amendments. On the contrary, the based on analysis of degradation temperatures, the TML allowed this discrimination together with their quantitative analysis. For example, added charcoal was not visible in TML from 320 to 330°C, which is used for carbon content determination. However, increasing quantities of charcoal were reflected in a higher TML around 520°C. Furthermore, differences between measured (with TML110–550 ) and predicted mass loss on ignition using both organic carbon (with TML330 ) and clay contents (with TML140 ) were confirmed as a suitable indicator for detection of organic amendments in different types of soils. We conclude that thermogravimetry enables the sensitive detection of organic fertilizers and organic amendments in soils under arable land use.